Complement Plays a Critical Role in Inflammation-Induced Immunoprophylaxis Failure in Mice - Escamilla-Rivera, Vicente; Santhanakrishnan, Manjula; Liu, Jingchun; Gibb, David R.; Forsmo, James E.; Foxman, Ellen F.; Eisenbarth, Stephanie C.; Luckey, C. John; Zimring, James C.; Hudson, Krystalyn E.; Stowell, Sean R.; Hendrickson, Jeanne E. (Frontiers in Immunology, 2021)
Complement impacts innate and adaptive immunity. Using a model in which the human KEL glycoprotein is expressed on murine red blood cells (RBCs), we have shown that polyclonal immunoprophylaxis (KELIg) prevents alloimmunization to transfused RBCs when a recipient is in their baseline state of heath but with immunoprophylaxis failure occurring in the presence of a viral-like stimulus. As complement can be detected on antibody coated KEL RBCs following transfusion, we hypothesized that recipient complement synergizes with viral-like inflammation to reduce immunoprophylaxis efficacy. Indeed, we found recipient C3 and C1q were critical to immunoprophylaxis failure in the setting of a viral-like stimulus, with no anti-KEL IgG alloantibodies generated in C3-/- or C1q-/- mice following KELIg treatment and KEL RBC transfusion. Differences in RBC uptake were noted in mice lacking C3, with lower consumption by splenic and peripheral blood inflammatory monocytes. Finally, no alloantibodies were detected in the setting of a viral-like stimulus following KELIg treatment and KEL RBC transfusion in mice lacking complement receptors (CR1/2-/-), narrowing key cells for immunoprophylaxis failure to those expressing these complement receptors. In-vitro studies showed complement fixed opsonized RBCs were significantly less likely to bind to B-cells from CR1/2-/- than wild type mice, potentially implicating lowered B-cell activation threshold in the presence of complement as being responsible for these findings. We thus propose a two-hit model for inflammation-induced immunoprophylaxis failure, where the first “hit” is recipient inflammation and the second “hit” is complement production/sensing. These results may have translational relevance to antigen-antibody interactions in humans.